(untitled) (Journal of the College of Basic Education, 2022)
The main purpose of this paper is to investigate hyperbole inbook blurbs. Back cover blurbs, brief texts displayed on book covers,provide information about a book to potential readers. They aremainly evaluative- persuasive texts which summarize the mainfeatures of the book and provide a mostly subjective evaluation usinglexical, pragmatic and textual devices. One of these devices ishyperbole. Hyperbole (also referred to as exaggeration oroverstatement) has been studied in rhetoric and literary contexts, butonly relatively recently in book blurbs. This paper aims to analyze andclassify hyperbolic constructions in back cover blurbs of selectedbooks in order to identify their pragmatic functions as evaluation andpersuasion. In order to achieve the aim of the present study, thirty book blurbsof linguistics and literary books were analyzed through adopting alinguistic and pragmatic model. The findings reveal that hyperbolicconstructions are realized widely via lexical devices especiallyadjectives. Moreover, most of the hyperbolic constructions used in theselected texts fulfill certain pragmatic functions among whichevaluation and emphasis are highly frequent. Based on this, hyperboleis primarily evaluative rather than a descriptive or explanatory device.Key words: hyperbole, book blurbs, pragmatic functions